Management of gastric cancer in older adults. Issue 6 (November 2017) - Matthaiou, Christiana; Papamichael, Demetris
Abstract: Gastric cancer is one of the most common malignancies worldwide with high incidence among older patients. While the evidence supports the use of adjuvant or peri-operative chemotherapy in operable gastric cancer, extrapolating these data for older individuals can be challenging. Strides have also been made in the management of metastatic disease with increasing use of second line and targeted therapies. Nevertheless, these advances have yet to translate to a clear benefit for older patients. These patients are under-represented in clinical trials, and the majority of data are extrapolated from subgroup analyses of randomised studies. Chronological age per se should not exclude treatment; however, some form of geriatric assessment should be considered for the evaluation for these patients.